Scalable Island Multicast for Peer-to-Peer Streaming. (8th February 2007) - Jin, Xing; Cheng, Kan-Leung; Gary Chan, S.-H.
Abstract : Despite the fact that global multicast is still not possible in today's Internet, many local networks are already multicast-capable (the so-called multicast "islands"). However, most application-layer multicast (ALM) protocols for streaming have not taken advantage of the underlying IP multicast capability. As IP multicast is more efficient, it would be beneficial if ALM can take advantage of such capability in building overlay trees. In this paper, we propose a fully distributed protocol called scalable island multicast (SIM), which effectively integrates IP multicast and ALM. Hosts in SIM first form an overlay tree using a scalable protocol. They then detect IP multicast islands and employ IP multicast whenever possible. We study the key issues in the design, including overlay tree construction, island management, and system resilience. Through simulations on Internet-like topologies, we show that SIM achieves lower end-to-end delay, lower link stress, and lower resource usage than traditional ALM protocols.